IMPLEMENTASI KEBIJAKAN TRANSPORTASI UMUM DI KOTA SEMARANG (STUDI KASUS PERUM DAMRI) - Oktavianti, Dinar Rizki; Lituhayu, Dyah (Journal of Public Policy and Management Review, 2017)
Act No. 22 of 2009 is a regulation that regulates the Traffic and Road Transportation which aims to realize the service of Traffic and Road Transportation which are convenient, secure, safe, orderly, smooth and integrated with other transportation modes to boost the national economy. Perum DAMRI is an organizer and a service provider bus-based public transportation which stipulating standardized electronic based service system that can improve the efficiency and effectiveness, so that it can be a superior transportation mode and is able to compete. This study aimed to describe and analyze how the Government and Perum DAMRI Semarang implement Act No. 22 of 2009 Article 213 on the build and developing facility and infrastructure of eco friendly Traffic and Road Transportation (LLAJ). The analysis techniques used to obtain the data were through the interview result with informants, observation, and supporting documents. This study used the theory of Merilee S. Grindlet which argues that the implementation motivating factor has three main factors, namely the policy content and policy environment, then the results of the implementation can be seen from the impact of the change in society. The result of this study indicates that the Implementation of Public Transport Policy in Semarang with Perum DAMRI Case Study is non optimal, with a decrease in performance and the level of provided service, resulting in a decrease in the interest of the passengers each year. Change that people want refers to the comfort, safety, and punctuality that currently have not been given yet by Perum DAMRI maximally. Recommendations that can be given are improving the performance and quality of service and doing innovation in order to provide the facility and infrastructure in accordance with the expectation of society.